2022
DOI: 10.3390/jpm12081302
|View full text |Cite
|
Sign up to set email alerts
|

Escaping the Reality of the Pandemic: The Role of Hopelessness and Dissociation in COVID-19 Denialism

Abstract: Background: Denialism of coronavirus disease 2019 (COVID-19) severely affected governments’ attempts to contain the spread of the virus. Indeed, groups of deniers showed scepticism and misinformation toward the causes of the virus, leading to less adherence to official guidelines and vaccination campaigns. The present study aimed to investigate the sociodemographic and psychological factors associated with COVID-19 denialism, expressed in the forms of scepticism, nonadherence to guidelines, and negative attitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 50 publications
0
1
0
2
Order By: Relevance
“…Относительный приоритет автономии личности над общественными потребностями во многих западных странах обусловлен доминирующей в этих государствах идеологией примата личной свободы и собственной траектории поведения человека. Между тем в последнее время западные государства, следуя концепции Nanny State, все чаще прибегают к использованию инструментов сдерживания деструктивного поведения своих граждан в отношении своего здоровья 15 .…”
Section: медицинский дениализм и интернетunclassified
See 1 more Smart Citation
“…Относительный приоритет автономии личности над общественными потребностями во многих западных странах обусловлен доминирующей в этих государствах идеологией примата личной свободы и собственной траектории поведения человека. Между тем в последнее время западные государства, следуя концепции Nanny State, все чаще прибегают к использованию инструментов сдерживания деструктивного поведения своих граждан в отношении своего здоровья 15 .…”
Section: медицинский дениализм и интернетunclassified
“…URL: https://lawphil.net/ 15. Путило Н. В., Волкова Н. С. Феномен Nanny state: новый вид государства или модификация государственного патернализма в современных условиях?…”
unclassified
“…Literature focusing on psychological factors such as attitudes [ 15 ], sense of control [ 16 ] and risk perception [ 17 , 18 ] suggests that adherence to pandemic contrast measures depends on their perceived efficacy [ 3 , 19 , 20 , 21 , 22 , 23 ], individual perceptions of stress [ 24 ], individual coping strategies [ 25 , 26 ], perceived self-efficacy [ 27 ], individual health beliefs [ 28 ], and perceived susceptibility to the virus [ 29 ]. Moreover, Ciacchella and colleagues [ 30 ] found that nonadherence was predicted by higher levels of dissociation, which in turn predicted low levels of sense of community and high levels of hopelessness. Such results were confirmed even in the Italian context.…”
Section: Introductionmentioning
confidence: 99%
“…Hopelessness can be a distressing consequence of the prolonged stress experienced by HCWs during the pandemic [33,44]. The overwhelming number of critically ill patients, limited resources, and witnessing high mortality rates can create a sense of despair and hopelessness.…”
Section: Introductionmentioning
confidence: 99%